Casimir interaction of arbitrarily shaped conductors. (1st March 2017) - Straley, Joseph P; Kolomeisky, Eugene B
Abstract: We review a systematic practical implementation of the multiple scattering formalism due to Balian and Duplantier (1977 Ann. Phys .104 300, 1978 Ann. Phys .112 165 ) for the calculation of the Casimir interaction between arbitrarily shaped smooth conductors. The leading two-point scattering term of the expansion has a simple compact form, amenable to exact or accurate numerical evaluation. It is a general expression which improves upon the proximity force and pairwise summation approximations. We show that for many geometries it captures the bulk of the interaction effect. The inclusion of terms beyond the two-point approximation provides an accuracy check and explains screening. As an illustration of the power and versatility of the method we re-evaluate sphere–sphere and sphere–plane interactions and compared the results with previous findings that employed different methods. We also compute for the first time interaction of a hyperboloid (mimicking an atomic force microscope tip) and a plane. We also analyze the anomalous situations involving long cylindrical conductors where the two-point scattering approximation fails qualitatively. In such cases analytic summation of the entire scattering series is carried out and a topological argument is put forward as an explanation of the result. We give the extension of this theory to the case of finite temperatures where the two-point scattering approximation result has a simple compact form, also amenable to exact or accurate numerical evaluation.